2011
DOI: 10.1111/j.1475-6773.2011.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Switching to a High-Deductible Health Plan on Use of Chronic Medications

Abstract: Switching to an HDHP that included modest drug copayments did not change medication availability or reduce use of essential medications for three common chronic illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…Between 2006 and 2011, the proportion of privately insured patients facing a deductible greater than $1000 increased from 10% to 31%. 9 Few diagnostic laboratory tests are exempt from these deductibles. The absence of information about laboratory test costs for patients and clinicians as well as the effect of these costs on clinical practice and care have been issues of concern for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2006 and 2011, the proportion of privately insured patients facing a deductible greater than $1000 increased from 10% to 31%. 9 Few diagnostic laboratory tests are exempt from these deductibles. The absence of information about laboratory test costs for patients and clinicians as well as the effect of these costs on clinical practice and care have been issues of concern for many years.…”
Section: Discussionmentioning
confidence: 99%
“…From 2006 to 2010 the percentage of employees covered by HDHPs with a deductible of at least $1000, increased from 10 percent to 27 percent [23]. In 2010, average deductibles for commercial health insurance plans ranged from $601 to $1903 for individuals and $1321 to $3780 for families [23], though the maximum out of pocket burden in 2015 is capped at $6,450 for self-only coverage or $12,900 for family coverage (IRS.…”
Section: The Underinsured: High Deductible Health Plansmentioning
confidence: 99%
“…For the past few decades there has been research around utilization of healthcare services with patients facing high cost sharing responsibility. The RAND Health Insurance Experiment of 1971 -1986 found that patients who are facing high-level cost-sharing reduced overall utilization by approximately 33 percent and total spending by about 30 percent [23].…”
Section: The Underinsured: High Deductible Health Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In addition, VBID has been incorporated into HDHPs, many of which now waive the deductible for selected types of preventive care (e.g., breast and cervical cancer screenings, and well-child visits) 33 and other treatments perceived to be of high value (e.g., medications for chronic conditions). 34 While VBID programs may consider CEAs only informally when identifying high-value care, they focus on clinical areas with the greatest potential to improve health outcomes and/or constrain costs, including the treatment of chronic illnesses (e.g., diabetes and antihypertensive medications) and secondary disease prevention (e.g., statins that lower cholesterol). 35 Early evidence suggests that such programs have been successful at meeting this potential.…”
Section: B Demand-side Initiativesmentioning
confidence: 99%